CHARACTERIZATION OF OPEN SOURCE AND FREE CODE TYPE LEADING SOLUTIONS TO DEPLOY DATA STORAGE AS A SERVICE - García Díaz, David; Díaz Crespo, Arturo; García Perellada, Lilia Rosa; garófalo Hernández, Alain Abel (Telemática, 2020)
Storage as a Service category is one of the Cloud Computing services with the highest adoption rate today. There is a lot of publicity and commercial information about the services of this nature by cloud service providers; however, the adoption of this service in small and medium-sized enterprises is still poor. Information on the possible options for the deployment of this service, especially those based on free and open-source software is also poor. The present work identifies and proposes a characterization of the main solutions to deploy Storage as a Service using free and open-source software in small and medium-sized enterprises. The proposal constitutes a tool that speeds up and facilitates the process of selecting this service. It impacts on the reduction of the time of the start-up of the service, as well as on the capital investments of the projects and on the operating expenses once the service is in operation.